Intimate Partner Violence and Hurricane Katrina: Predictors and Associated Mental Health Outcomes - Schumacher, Julie A.; Coffey, Scott F.; Norris, Fran H.; Tracy, Melissa; Clements, Kahni; Galea, Sandro (Violence and victims, 2010)
This study sought to establish the prevalence and correlates of intimate partner violence (IPV) victimization in the 6 months before and after Hurricane Katrina. Participants were 445 married or cohabiting persons who were living in the 23 southernmost counties of Mississippi at the time of Hurricane Katrina. Data for this study were collected as part of a larger, population-based, representative study. The percentage of women reporting psychological victimization increased from 33.6% prior to Hurricane Katrina to 45.2% following Hurricane Katrina (p < .001). The percentage of men reporting psychological victimization increased from 36.7% to 43.1% (p = .01). Reports of physical victimization increased from 4.2% to 8.3% for women (p = .01) but were unchanged for men. Significant predictors of post-Katrina victimization included pre-Katrina victimization, age, educational attainment, marital status, and hurricane-related stressors. Reports of IPV were associated with greater risk of post-Katrina depression and posttraumatic stress disorder. Data from the first population-based study to document IPV following a large-scale natural disaster suggest that IPV may be an important but often overlooked public health concern following disasters.